UPAYA MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM CENTERED LEARNING (PCL) DI SMA NEGERI 1 ANGKOLA BARAT - Marisa Lusiana Siregar; Wiwiik Novitasi; Lisna Agustina (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2019)
This type of research is Research Action class (Classroom action Research). While  the techniques and data collection tool that is the test, and observations. Mathematical literacy ability test percentage of students on a cycle I was 63% to 82% in cycle II. With the amount of the percentage increase in the students' mathematical literacy ability tests of 19%, activity levels of students learning math increases, it is retrieved from the percentage of 63% levels of math learning activities cycle I, and 82% in cycle II rose to 19% and the ability to manage teacher learning percentage of 74% in cycle I and 94% in cycle II, with an increase of 20%, and the results of this study showed that the model of learning Problem Centered Learning (PCL) can improve mathematical literacy ability of the students in class X IPS 2 SMA Negeri 1 West Angkola. Keywords: Problem Centered Learning (PCL) learning model, literacy